Sinergitas Stakeholder Pengembangan Halal Fashion di Indonesia - Muhammad Ahsanul Amal (Jurnal Ilmiah Ekonomi Islam, 2023)
The size of the Muslim population in Indonesia and the demographic bonus are factors in increasing the halal industry. The halal industry in Indonesia covers not only the halal food sector but also other sectors such as Islamic finance, halal travel, halal fashion, halal cosmetics and pharmaceuticals, and halal media end recreation. According to the State of the Global Islamic Economy Report 2022, Indonesia is still under the United Arab Emirates and Turkey and cannot become the world's center for halal fashion. Therefore halal fashion development model is needed so that Indonesia can compete with that country. This research aims to initiate a model of halal development in Indonesia. The approach used is descriptive analysis with secondary data. Research data was collected from books, articles, and reports published by relevant agencies, which were then reduced by data so that researchers could interpret the data collection results and conclude the research results. As for the results of research conducted on several sources, researchers found a halal fashion development model, where in this development model, the synergy of all elements is required, starting from the government, society (producers, distributors, and consumers), Islamic financial institutions, and research institutions and universities. to realize Indonesia as the center of world halal fashion. This synergy is needed so local people can look at halal fashion products produced by Indonesian designers. Not only importing products from abroad. Because domestic halal fashion products are no less competitive than products found abroad.